Academic Nexus Program: Catalysing Research Collaboration through USU-UiTM 4–10 September 2023 / Zamri Ahmad …[et al.] - Ahmad, Zamri; Azmi, Azila; Ramaiah, Angayar Kanni; Mohd Kamal, Saiful Bahri (UiTM Global @ Office of International Affairs, 2024)
A group of lecturers from Universiti Teknologi MARA, Pulau Pinang Branch, were invited to attend the Academic Nexus Programme (ANP): Catalysing Research Collaboration Through USU-UiTM, held at Universitas Sumatera Utara (USU), Indonesia from 4 to 9 September 2023. The invitation was part of the Strategic Research Partnership Grant and Memorandum of Agreement (MoA) established between the Faculty of Law at USU, Medan, Indonesia, and Universiti Teknologi MARA (UiTM) Pulau Pinang Branch, Malaysia, on 11 January 2023. The programme was led by Assoc. Prof. Dr. Azila Azmi from the Faculty of Hotel and Tourism Management, UiTM Pulau Pinang Branch. Key activities during the programme included a focus group discussion with stakeholders in the Medan tourism industry, international community service, guest lectures, public lectures, and an official meeting with the USU Rector.